Continuity and crisis in German cinema, 1928-1936 - Hales, Barbara, 1962-; Petrescu, Mihaela, 1974-; Weinstein, Valerie, 1971- (Camden House, 2016)
Hitler's Machtergreifung, or seizure of power, on January 30, 1933, marked the end of the Weimar Republic and the beginning of the Third Reich, and German film scholarship has generally accepted this date as the break between Weimar and Nazi-era film as well. This collection of essays interrogates the continuities and discontinuities in German cinema before and after January 1933 and theirrelationship to the various crises of the years 1928 to 1936 in seven areas: politics, the economy, concepts of race and ethnicity, the making of cinema stars, genre cinema, film technologies and aesthetics, and German-international film relations. Focusing both on canonical and lesser-known works, the essays analyze a representative sample of films and genres from the period. This book will be ofinterest to scholars and students of Weimar and Third Reich cinema and of the sociopolitical, economic, racial, artistic, and technological spheres in both late Weimar and the early Third Reich, as well as to film scholars in general. Contributors: Paul Flaig, Margrit Frölich, Barbara Hales, Anjeana Hans, Bastian Heinsohn, Brook Hnyuel, Kevin B. Johnson, Owen Lyons, Richard W. McCormick, Kalani Michell, Mihaela Petrescu, Christian Rogowski, Valerie Weinstein, Wilfried Wilms. Barbara Hales is Associate Professor of History at the University of Houston-Clear Lake. MihaelaPetrescu is Visiting Lecturer at the University of Pittsburgh. Valerie Weinstein is Assistant Professor of Women's, Gender, and Sexuality Studies and German Studies at the University of Cincinnati.
Keywords: Motion pictures -- Germany -- History -- 20th century.; Motion pictures -- Social aspects -- Germany -- History -- 20th century.; Motion pictures -- Political aspects -- Germany -- History -- 20th century.; Cinéma -- Allemagne -- Histoire -- 20e siècle.; Cinéma -- Aspect social -- Allemagne -- Histoire -- 20e siècle.; Cinéma -- Aspect politique -- Allemagne -- Histoire -- 20e siècle.; PERFORMING ARTS -- Reference.; PERFORMING ARTS -- Film & Video -- History & Criticism.; Motion pictures; Motion pictures -- Political aspects; Motion pictures -- Social aspects; Germany; 1900-1999; European history.; German cinema.; Hitler.; Nazism.; World War II.; anthropology.; film scholarship.; film studies.; history of film.; media studies.; sociology.; twentieth century Germany.; History